Fever, 1793 - Anderson, Laurie Halse (New York : Aladdin Paperbacks, 2002)
In 1793 Philadelphia, sixteen-year-old Matilda Cook, separated from her sick mother, learns about perseverance and self-reliance when she is forced to cope with the horrors of a yellow fever epidemic.
Ages 10 and up.
Keywords: Yellow fever -- Pennsylvania -- Philadelphia -- Fiction; Epidemics -- Fiction; Survival -- Fiction; Pennsylvania -- History -- 1775-1865 -- Fiction; Philadelphia (Pa.) -- Fiction